PENGEMBANGAN MEDIA DAN LKPD PEMBELAJARAN IPA BERBASIS PENDEKATAN SETS PADA MATERI PENCEMARAN LINGKUNGAN UNTUK KELAS VII SMP - Ayuningsih, Nina Oktavia; Zulhelmi, Zulhelmi; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:The use of learning media is very important. However, the learning media has not been used optimally. Based on the results of observations in junior high school, students are still lacking in maximizing learning media for environmental pollution materials. This is because students cannot directly observe the object of pollution during learning. For this reason, it is necessary to develop learning worksheets media that are equipped with experimental media complete with the need for tools and materials based on the SETS approach to cognitive learning outcomes and students' environmental care attitudes. This study aims to describe the development and validity of learning media and worksheets based on the SETS approach, as well as the students' environmental care attitude. This type of research uses Research and Development (R&D) development research methods with a 4-D model, namely Define, Design, Defelopment and Dessimination. In this study, modifying it into two stages, namely the design and development stages. The SETS approach-based learning worksheet media that will be developed are validated first by physics education lecturers. The types of data to be obtained in this study are quantitative and qualitative data. Quantitative data in the form of validity values from the media and LKPD and qualitative data obtained from input from the validator. The data collection instruments used were in the form of LKPD media validation sheets and experimental tools. The data were analyzed descriptively to determine the validity of the LKPD media using Aiken's V. The results showed that the overall validity of the LKPD media was valid with Aiken's validity index of 3,34.And the validity of the experimental media is 3.18.So it can be concluded that the SETS approach-based science learning media on environmental pollution material for class VII SMP is declared valid based on the assessment aspect on the validation sheet.Keywords: LKPD Media, SETS, Environmental Pollution